2017
DOI: 10.1002/jclp.22532
|View full text |Cite
|
Sign up to set email alerts
|

The client's perspective on (experiences of) psychotherapy: A practice friendly review

Abstract: Recent decades have seen a significant increase in the number of studies exploring client perspectives on, and experiences of, psychotherapy. The present article provides a practice friendly overview of this research, identifying common domains of inquiry, and providing examples of findings relevant to practitioners. Research in this area can be categorized in terms of the client's perspective pertaining to theoretical constructs, studies of client satisfaction, and qualitative studies that are either open-end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 37 publications
(75 reference statements)
4
47
0
Order By: Relevance
“…This research suggests that the goals of patients depend heavily on the stage in their lives and circumstances. One recent study identified several categories of helpful outcomes of psychotherapy, including awareness, insight, and selfunderstanding, behavioral change, and solution of problems, empowerment, relief, the better understanding of feelings, the reassurance and support from the therapist, and the personal contact with the therapist [5]. Another study was based on indepth qualitative interviews with patients [6], and found four categories of outcomes which were considered by patients to be the most important: (1) Establishing new ways of relating to others;…”
Section: Patient-defined Outcomes In Mental Health Treatmentmentioning
confidence: 99%
“…This research suggests that the goals of patients depend heavily on the stage in their lives and circumstances. One recent study identified several categories of helpful outcomes of psychotherapy, including awareness, insight, and selfunderstanding, behavioral change, and solution of problems, empowerment, relief, the better understanding of feelings, the reassurance and support from the therapist, and the personal contact with the therapist [5]. Another study was based on indepth qualitative interviews with patients [6], and found four categories of outcomes which were considered by patients to be the most important: (1) Establishing new ways of relating to others;…”
Section: Patient-defined Outcomes In Mental Health Treatmentmentioning
confidence: 99%
“…Moments where clients approach their inner experiences and explore these verbally and non-verbally with the therapist are shown to build and strengthen the therapeutic relationship (Timulak and Keogh, 2017;Gelso et al, 2018), and the therapeutic relationship is well documented as important to the outcome of therapy (Flückiger et al, 2018). Moreover, studies show that it might be beneficial when the therapeutic alliance is established early-e.g., by the fifth session of therapy (Bohart and Wade, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Existing qualitative studies have consistently found that clients appreciate an understanding, warm, caring and engaged therapist (Orlinsky and Howard, 1967; Toukmanian and Rennie, 1992; Levitt et al, 2006; Timulak, 2007; Israel et al, 2008; Mortl and Von Wietersheim, 2008; Watson, 2018). Previous research on the clients’ perspectives particularly point to the importance of the caring and supportive relationship (Labott et al, 1992; Timulak and Elliott, 2003; Levitt et al, 2016; Timulak and Keogh, 2017; Timulak et al, 2017). In a meta-analysis of 109 qualitative studies of clients’ experiences of psychotherapy, Levitt et al (2016) found that authentic caring from the therapist allowed clients to feel validated and engage in vulnerable discussion, but that overinvolvment could also hinder client’ sense of agency.…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis of 109 qualitative studies of clients’ experiences of psychotherapy, Levitt et al (2016) found that authentic caring from the therapist allowed clients to feel validated and engage in vulnerable discussion, but that overinvolvment could also hinder client’ sense of agency. Timulak and Keogh (2017) highlight that clients emphasize the warmth, authenticity, honesty and dedication of the therapist during the formation of the therapeutic relationship. In this article, our main focus is to investigate how clients experience the role of the therapeutic relationship within the context of EFT.…”
Section: Introductionmentioning
confidence: 99%